Analisis Penerapan RME di Poliklinik Reguler Rawat Jalan RSUD Kota Salatiga Menggunakan Metode HOT-Fit - Aryawan Eka Syahputra; Widiyanto, Wahyu Wijaya; Widiyoko, Aries (Journal Health Information Management Indonesian (JHIMI), 2025)
The advancement of information systems requires every health facility to implement Electronic Medical Records (EMR) in accordance with Minister of Health Regulation No. 24 of 2022. Salatiga City Hospital has been using the EMR system since 2023, but obstacles such as system disruptions during peak hours and features that are not relevant to the needs of officers were found.The purpose of this study was to analyze the implementation of EMR in the Regular Outpatient Polyclinic of Salatiga City Hospital based on the Human, Organization, Technology, and Net Benefit (HOT-FIT) approach. This study used a quantitative descriptive method with a purposive sampling technique. With 43 respondents consisting of health workers. Data were collected through questionnaires and in-depth interviews, then analyzed using descriptive statistics. The results showed that the Human aspect had a respondent achievement rate (TCR) of 76.2% in the Good category, but the training aspect was still less than optimal and user satisfaction was not optimal due to technical constraints. The Organization aspect was 74,0% in the Good category, but management support was not optimal. Technology aspect 72.5% in the Good category, indicating a fairly good system even though errors often occur during peak hours, features that are less relevant and the ability of the person in charge is less than optimal. Net Benefit aspect 77.5% in the Good category, but there are still input errors due to human error. The conclusion of this study shows that the implementation of RME is running Well, but improvements are needed in user training and strengthening of technology infrastructure to support the success of the system.